ANALISIS NILAI TAMBAH DAN KEMAMPULABAAN TIGA AGROINDUSTRI VCO D1 KOTA BENGKULU - Nabiu, Musryadi; Yuliarti, Ellys; Manurung, Esteria (Jurnal AGRISEP, 2006)
This research was did on Bengkulu town at June until July 2006 with purpose to know how many VCO agroindustry can create the value added, profit level and  efficiency level of production cost structure from 3 VCO  industries  in Bengkulu town. Location Determination  Method is by purposive  with reason that VCO agroindustri  in Bengkulu  town have existing  and property  commercial.  Respondent  determination method  is by purposive,  sum samples  in this  research  are three  VCO agro industry.  Data used in this research, are primary and secondary.   analysis method in this research  are value added of processing, Break  Event  Point  (BEP)     and  profltability.Analisis   yield   Value  Added  processing   1 grain  coconut processing  are  VCO Dara 2.5761Btr, NeoVico  Rp 2.05218tr and  VCO Raffesia Rp 2. 1951Btr.Total high more fix cost are VCORaffesia  Rp 1.548.747 (57,72 %) / pp, and VCO Dara Rp 609.413 (22,7 %)/pp and than low is rank  fix cost"  NeOVico Rp   524.751  (19,55  %)/pp.  Total high more  variabel cost are  VCO Raflesia   Rp  2.628.410   (55,33   %)/pp  and  than  low  is  rank   variabel   cost  NeoVico  Rp   1.182.596 (34, 25%)/pp.  Profitability  for  VCO  Dara  agroindustri   at juny/pp   large  Rp  1.834.000  (55%),  NeoVico agroindustri  large Rp Rp1.679.370 (50 %)/pp and VCO Raflesia large 3.615.300 (46 %)/pp.